The influence of potassium content on octahedral-tilt disorder in Na0.5Bi0.5TiO3-solid solutions near morphotropic phase boundary. (15th July 2018) - Neagu, Alexandra; Tai, Cheuk-Wai
Abstract: A semi-quantitative comparison of 3D electron diffraction data revealed structural differences at the nanoscale for three (95- x )Na0.5 Bi0.5 TiO3 - x K0.5 Bi0.5 TiO3 -5BaTiO3 solid solutions close to the morphotropic phase boundary, with x  = 0, 5, 10. Using a novel rotation electron diffraction technique, diffuse scattering intensity was recorded in 3D as continuous rods along hk0 . 5 reciprocal-planes. By analyzing the different superstructure reflections and the intensity/morphology of diffuse scattering, a structural model of the local octahedral-tilt disorder for the different ceramics was developed. A good agreement was obtained between the experimental and simulated data with a model comprising of antiphase ( a − a − a − ) and plate-like in-phase ( a 0 a 0 c + ) nanodomains. Graphical abstract: Unlabelled Image